MANOBHAARAMAKATTOO MANASAKTHI NETOO - ROBERT A SCHULLER; CHANDRA VAKAYIL (KOTTAYAM D C BOOKS, 2018)
Through enlightening personal anecdotes and straightforward counsel, the author offers the assurance that God always showers blessings upon us, even in times of pain and affliction, and show the way toward healing with twelve tried-and-true, biblically-based steps for achieving life-changing powers.
Keywords: BIBLE- MEDITATION -- RELIGION ASPECTS - CHRISTIANITY -- COMPULSIVE BEHAVIOUR